The RNA-binding protein HuR is required for maintenance of the germinal centre response - Ines C. Osma-Garcia (Nature Portfolio, 2021)
Germinal centre (GC) responses may require RNA binding proteins (RBP) for post-transcriptional gene regulation. Here the authors show the RBP HuR supports GCs by promoting Myc and Myc-dependent transcription to enhance antigen-specific GC B cell selection and production of high affinity antibodies.